FROM CHURCH LIFE IN POBEREZHZHJA: THE SHOWER: HISTORICALLY-RELIGIONS ASPECTS - Руско, Н. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article considers the main milestones of the history of the spiritual life of the village of Poberezhzhya of Tysmenytsja district of Ivano-Frankivsk region. The peculiarities of building the Borisoglebsky monastery on the mountain Murovanka near the settlement are revealed. There are written references to Churches in the village of Poberezhzhya, as well as statistics of this parish. It tells about the priests of this church and about the modern temple in Poberezhzhya. On the basis of chematists, documents of the National Museum of Metropolitan Andrey Sheptytsky in Lviv, visits by Joseph Shumlyansky, important historical moments in the history of the church.